Ethnobotany of Medicinal Plants used by the Talaandig Tribe in Brgy. Lilingayon, Valencia City, Bukidnon, Philippines - Odchimar, Nyzar Mabeth O.; Nuñeza, Olga M.; Uy, Mylene M.; Senarath, W.T.P.S.K. (Asian Journal of Biological and Life Sciences, 2017)
This paper presents the ethnobotanical documentation on the medicinal plants used by the Talaandig tribe in Brgy. Lilingayon, Valencia City, Bukidnon, Philippines. The documentation was done through informal interviews of key informants including the Tribal leader and a subordinate healer. The ethnobotanical survey documented 66 species of medicinal plants belonging to 38 families. Families Asteraceae and Poaceae are the most represented with five species each. Skin diseases and women-related diseases are the most common health problems traditionally treated by the documented medicinal plants. Decoction is the most common method of preparation followed by direct application of the fresh plant part. The leaves are the most commonly used plant part. Results indicate that indigenous medicinal plants are good sources of plant-based safe drugs.
Keywords: Asteraceae; diseases; healer; Poaceae